The Role of Astrocytes in Multiple Sclerosis - Ponath, Gerald; Park, Calvin; Pitt, David (Frontiers in Immunology, 2018)
The role traditionally assigned to astrocytes in the pathogenesis of MS lesions has been the formation of the glial scar once inflammation has subsided. Astrocytes are now recognized to be early and highly active players during lesion formation and key for providing peripheral immune cells access to the CNS. Here, we review the role of astrocytes in the formation and evolution of MS lesions, including the recently described functional polarization of astrocytes, discuss prototypical pathways for astrocyte activation, and summarize mechanisms by which MS treatments affect astrocyte function.